Botulinus Toxin (âBotoxâ) - Edward J. Wood; Amanda North (Jurnal Matematika & Sains, 2005)
The toxin produced by the bacterium Clostridium botulinum is one of the most lethal toxins known. The structure of the type A toxin has been solved by x-ray crystallography and this reveals how the toxin acts. The 150kDa molecule is in three parts, a receptor-binding domain that enables it to bind to nerve cells, a translocation domain that enables the toxin to enter the cells, and a protease domain that specifically digests proteins concerned with the delivery of the neurotransmitter acetylcholine at the neuromuscular junction leading to paralysis of the muscles required for breathing. Despite its highly lethal nature the type A toxin, as BotoxÂ®, is used medically in tiny doses to treat a number of clinical conditions, and more recently cosmetically, to remove wrinkles and frown lines.